Com quem podemos contar? Autoridade, Empoderamento e Responsabilização em Moçambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (Portuguese Translation of IDS Working Paper 546, Maputo: Instituto de Estudos Sociais e Económicos, 2021)
Neste artigo, usamos 'diários de governação' para analisar as interações entre pessoas pobres e autoridades em contextos de Fragilidade, Conflitos e Violência (FCVAS) em Moçambique. Questionamos os significados de empoderamento e responsabilização, sob ponto de vista de pessoas pobres e marginalizadas, e procuramos perceber como essas pessoas vêem as instituições que as governam, incluindo as que as providenciam bens e serviços básicos, entre os quais os de saúde e segurança. As conclusões mostram que, mesmo que as percepções e, com elas, os conceitos de empoderamento e responsabilização que emergiram, não difiram significativamente dos identificados na literatura, em termos de ação e mobilização há diferenças. Constatamos que, nos nossos locais de pesquisa, as pessoas raramente se mobilizam, mesmo com a má prestação de serviços básicos e a prevalência de injustiças. Muitos consideram-se 'incapazes' de influenciar ou forçar as 'autoridades' a responderem às suas preocupações e demandas. Por 'Autoridade Pública' entendem qualquer entidade ou pessoa capaz de resolver os problemas da comunidade, enquanto Estado, geralmente reconhecido como 'Autoridade', é percebido como indistinto do Partido Frelimo e do Governo, mas também é visto como um pai, embora ausente, e aquele que se esquece e abandona os seus filhos.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

Who Can We Count On? Authority, Empowerment and Accountability in Mozambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (IDS Working Paper 546, Brighton: Institute of Development Studies, 2021)
In this paper, we explore the use of a governance diaries methodology to investigate poor households’ interactions with authority in fragile, conflict and violence-affected settings in Mozambique. The research questioned the meanings of empowerment and accountability from the point of view of poor and marginalised people, with the aim of understanding what both mean for them, and how that changes over time, based on their experiences with governance. The study also sought to record how poor and marginalised households view the multiple institutions that govern their lives; providing basic public goods and services, including health and security; and, in return, raise revenues to fund these services. The findings show that, even if the perceptions and, with them, the concepts of empowerment and accountability that emerged do not differ significantly from those identified in the literature, in terms of action and mobilisation there are distinctions. In our research sites we found that people rarely mobilise, even faced with prevalent injustices and poor basic service provision. Many claim to be ‘unable’ to influence or force ‘authorities’ to respond to their concerns and demands.
Accepted: 2021-02-02T10:30:54Z
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

Health, development, and institutional factors: The Mozambique case - Garrido, Paulo Ivo (2020)
Abstract: The central aim of this text is to show the impact institutions have on the performance of the health sector in Mozambique. The text shows that of the social determinants of health, institutions play a central role in the performance of the Mozambican health sector—and, through it, economic and social development—particularly for the poorer and more vulnerable, such as children, women, the disabled, and the elderly. It is also argued that the deficiencies and inefficiencies of the operation of the health sector in Mozambique are largely the result of the fact that the institutions with influence on the health sector are controlled by a minority of privileged people who do not give the appropriate priority to the basic health needs of the majority of the population. Finally, it is argued that the most important institutional measures for improving the state of health of Mozambicans are the revision of the Constitution of the Republic, the strengthening of the National Health System (particularly the National Health Service), and the reduction of poverty and economic and social inequality.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; health - social determinants of health / saúde - determinantes sociais da saúde; health / saúde; institutions / instituições

Saúde, desenvolvimento e factores institucionais: o caso de Moçambique - Garrido, Paulo Ivo (2020)
Este texto tem por objectivo central mostrar o impacto que as instituições têm no desempenho do sector da Saúde em Moçambique. No texto demonstra-se que, de entre os Determinantes Sociais da Saúde, as instituições têm um papel central no desempenho do sector da Saúde — e, por seu intermédio, no desenvolvimento económico e social — dos moçambicanos, em especial dos mais pobres e mais vulneráveis, como as crianças, as mulheres, as pessoas com deficiência e os idosos. Argumenta-se também que as deficiências e ineficiências do funcionamento do sector da Saúde em Moçambique resultam em larga medida do facto de as instituições com influência no sector da Saúde serem controladas por uma minoria de privilegiados que não dá a prioridade devida às necessidades básicas em saúde da maioria da população. Finalmente, argumenta-se que as medidas de carácter institucional mais importantes para a melhoria do estado de saúde dos moçambicanos são a revisão da Constituição da República, o reforço do Sistema Nacional de Saúde (em particular do Serviço Nacional de Saúde) e a redução da pobreza e das iniquidades económica e social.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; access to services / acesso a serviços; accountability / responsabilização; health - social determinants of health / saúde - determinantes sociais da saúde; health / saúde; institutions / instituições

Capacity Strengthening in the Least Developed Countries (ldcs) for Adaptation to Climate Change (clacc): Climate Change and Health in Mozambique - Bambaíge, Albertina João; Cuamba, Boaventura; Hauengue, Maria dos Anjos (International Institute for Environment and Development (IIED), 2008)
The relationship between climate change and its effects on human health has been widely studied. Increases in temperature and variations in precipitation can exacerbate a number of human diseases including respiratory infections, malnutrition, vector and water borne diseases such as malaria and cholera. Besides all efforts undertaken by the Mozambican Government to reduce poverty and meet the MDGs targets, it is clear that climate change effects will influence negatively in meeting these targets. Damages caused by floods in Mozambique undermine economic growth rates of the country. Mainstreaming climate change adaptation into government policies would strengthen the capacity of the country to deal with climate change impacts. Climate change is a reality and the impacts on health are great with the poor at most risk. Efforts must be done nationally at all levels to come up with a proactive approach since all actors in the Mozambican society are directly or indirectly affected. This must include clear policies and strategies to deal with impacts of climate change on health; intersectoral approaches for strengthening the implementation of these policies and a greater support from those wealthy in resources and knowledge for minimizing the risks and increase community's adaptation capacity. The case study included in this country report highlights the relationship between climate change and human health through an analysis of malaria and cholera data taking the example of the 2000/2001 floods, which were considered the worst in the last fifty years. Adaptation practices and the adaptive capacity of the country during floods periods, policies and strategies are also discussed.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; climate change / mudanças climáticas; government policy / politica governamental; health / saúde; institutions / instituições; natural disasters / desastres naturais